PREVALENCE QUALITY OF LIFE IN STUDENTS WITH SYMPTOMS OF SELF-INJURY - Medina, Agnis; Sugara, Gian Sugiana; Isti’adah, Feida Noorlaila (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to identify and analyze the general overview of the quality of life among 12th-grade students at SMAN 4 Tasikmalaya exhibiting self-harm symptoms. Employing a quantitative method with a descriptive design, the study involved 287 participants. Two instruments were utilized: the Deliberate Self-Harm Inventory (DSHI), developed by Gratz (2001), consisting of 17 items measuring the frequency, severity, duration, and types of self-harm behavior; and the Adolescent Quality of Life Inventory (AQoLI), adapted from an instrument created by Ependi (2022). This latter instrument measures adolescent quality of life through 26 items across three dimensions: personal growth, social functioning, and self-functioning. The findings reveal that 49% of the students (142 individuals) had engaged in at least one form of self-harm. The quality of life among students with self-harm symptoms was categorized as very high (11%), high (58%), average (30%), and low (1%). This study concludes that self-harm symptoms among 12th-grade students at SMAN 4 Tasikmalaya are generally mild. However, attention is needed through counseling and guidance services to provide interventions that support emotional regulation and strengthen aspects of life, serving as essential means to help students build healthy coping mechanisms and enhance their well-being.